Diversity of forest floor vegetation in Napabalano Nature Reserve and Warangga Protection Forest, Southeast Sulawesi - Sulistijorini Sulistijorini; Ilma Rahmawati; Ibnul Qayim (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.